2016
DOI: 10.1097/cmr.0000000000000243
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporin 1 protein expression is associated with BRAF V600 mutation and adverse prognosis in cutaneous melanoma

Abstract: Despite experimental findings suggesting the prognostic significance of Aquaporin 1 (AQP1) in human melanoma, no published clinical data are available. We studied the expression of AQP1 protein in cutaneous melanoma, correlated our findings with standard histological and genetic markers, and long-term clinical follow-up. Our study evaluated the AQP1 protein expression in 78 melanoma patients, representing two predefined risk cohorts using the immune labeling technique with commercially available anti-AQP1 anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 23 publications
(22 reference statements)
2
8
0
Order By: Relevance
“…Namely, a statistically significant association of AQP‐1 high expression with increased survival was observed with a median OS of 12 months for patients with ≥50% AQP‐1 expression vs a median OS of only 7 months for patients with less than 50% AQP‐1 expression. The relationship between higher levels of AQP‐1 in MM and a better prognosis confirms the results of previous studies, but appears to be in conflict with data reported in other tumours, including breast cancer, melanoma, urothelial carcinoma and pharyngeal squamous cell carcinoma, in which increased levels of AQP1 are associated with a poorer prognosis . These data and the relatively few studies on MM require further validation.…”
Section: Discussionsupporting
confidence: 55%
“…Namely, a statistically significant association of AQP‐1 high expression with increased survival was observed with a median OS of 12 months for patients with ≥50% AQP‐1 expression vs a median OS of only 7 months for patients with less than 50% AQP‐1 expression. The relationship between higher levels of AQP‐1 in MM and a better prognosis confirms the results of previous studies, but appears to be in conflict with data reported in other tumours, including breast cancer, melanoma, urothelial carcinoma and pharyngeal squamous cell carcinoma, in which increased levels of AQP1 are associated with a poorer prognosis . These data and the relatively few studies on MM require further validation.…”
Section: Discussionsupporting
confidence: 55%
“…In other types of malignancy, there has been variability in the significance of AQP1 expression levels associated with survival outcomes and tumor phenotype (15,16,24-27). The association between high AQP1 expression and poor prognosis was demonstrated in numerous types of solid cancer, including lung (15,24), breast (16,25), ovarian (26) and cutaneous melanoma cancer (27). In accordance with this, the upregulation of AQP1 was associated with aggressive subtypes of brain tumors (28,29) and cervical cancer (30).…”
Section: Discussionsupporting
confidence: 53%
“…Normal mesothelial cells express AQP1 at the apical aspect of the cells, whereas MMs show loss of polarity of AQP1 expression, or a complete loss of AQP1 labelling [ 7 ]. The situation in MM, where higher levels of AQP1 are related to better prognosis is unlike that in other tumours, where increased levels of AQP1 are associated with poorer prognosis, including breast cancer, melanoma, urothelial carcinoma and pharyngeal squamous cell carcinomas [ 18 , 19 , 20 , 21 , 22 ]. Interestingly, in some of these tumours AQP1, a membrane bound protein, was found within the cytoplasm [ 21 ].…”
Section: Discussionmentioning
confidence: 99%